Zinc and bacterial adherence. - Sugarman, B (1982)
Zinc significantly enhances the ability of piliated Gram-negative and Gram-positive bacteria to attach to HeLa cells. This effect is related to the concentration of zinc and degree of bacterial piliation, and is not present with unpiliated organisms. Bacterial viability is not necessary for this effect, and sulfhydryl blockers decrease the response. These data suggest that zinc can bind to bacterial pili and augment bacterial adherence; in this manner, zinc may act as a virulence factor.